OPTIMALISASI PENGELOLAAN KELAS MELALUI MODEL PEMBELAJARAN ENJOYFULL LEARNING BERBASIS LITERASI DI SMA BERBASIS PONDOK PESANTREN - Ayyu Subhi Farahiba; Emy Rizta Kusuma (Universitas Mataram, 2022)
Distance Learning (PJJ) which was carried out during the COVID pandemic was one of the factors causing academic decline (learning loss). To overcome the problem of academic decline, teachers need to optimize learning through the application of enjoyful learning. Joyful learning is a learning strategy that seeks to generate interest, full involvement, and the creation of meaning, understanding of values that make students happy. This activity aims to: (1) carry out workshops for teachers to prepare a Learning Planning Plan (RPP) for enjoyful learning, and (2) produce learning tools in the form of lesson plans that apply the joyful learning model. Service activities are carried out in three stages of activity, namely preparation, implementation, and evaluation. Preparation is carried out by conducting a preliminary survey to see conditions in the field regarding the development of the teaching profession. The implementation is carried out by training (workshops), using the lecture method, namely presentation techniques, followed by question-answer discussions and exercises as a form of workshop activities for the preparation of learning tools. Evaluation of activities is carried out for each stage by collecting and concluding data from each stage of activity. The service activities carried out were in the form of assistance in the preparation of RPP joyful learning by 25 teachers of ITMA (Islam Terpadu Misykat Al-Anwar) SMA and one principal on November 23, 2021. Thus, the result of this activity is the RPP's enjoyful learning that has been prepared by the teachers as an outcome of the service activities that have been carried out. This service activity is carried out in several stages to obtain maximum results in the preparation of RPP enjoyful learning. RPP enjoyful learning that has been prepared, then actualized in learning activities at SMA ITMA. The actualization activity aims to determine the effectiveness of the workshops that have been carried out and to maximize the results of developing lesson plans that have been prepared by the teachers